2009
DOI: 10.1080/09540260902962107
|View full text |Cite
|
Sign up to set email alerts
|

The functional neuroanatomy of bipolar disorder

Abstract: In this manuscript, research articles using functional magnetic resonance imaging (fMRI) to study adult patients with bipolar disorder were reviewed. The findings from these studies identify altered brain activation in five regions in cortico-limbic pathways responsible for emotional regulation: portions of the prefrontal cortex; anterior cingulate cortex; amygdala; thalamus; and striatum. The most consistent findings were overactivation of amygdala, striatum, and thalamus. Findings in prefrontal cortex were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 33 publications
4
79
0
5
Order By: Relevance
“…However, there were also two regions that had a stronger relationship between these imaging modalities in the bipolar versus healthy control group (i.e., coupling was enhanced), the left temporal pole and left inferior temporal gyrus. Many of these regions have been previously implicated by functional imaging studies as having a role in bipolar disorder (Cerullo, Adler, Delbello, & Strakowski, 2009; Gruber, Rogowska, & Yurgelun‐Todd, 2004; Keener & Phillips, 2007; Maletic & Raison, 2014; Strakowski et al., 2011; Townsend et al., 2012; Whitton, Treadway, & Pizzagalli, 2015; Yoshimura et al., 2014), which suggests that the altered relationship between fT1ρ and BOLD is related to the illness. For instance, numerous studies have shown that functional activity in the striatum is altered in bipolar disorder during the completion of reward tasks (Caseras, Lawrence, Murphy, Wise, & Phillips, 2013; Whitton et al., 2015; Yip, Worhunsky, Rogers, & Goodwin, 2014) and reduced during fear perception tasks (Killgore, Gruber, & Yurgelun‐Todd, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were also two regions that had a stronger relationship between these imaging modalities in the bipolar versus healthy control group (i.e., coupling was enhanced), the left temporal pole and left inferior temporal gyrus. Many of these regions have been previously implicated by functional imaging studies as having a role in bipolar disorder (Cerullo, Adler, Delbello, & Strakowski, 2009; Gruber, Rogowska, & Yurgelun‐Todd, 2004; Keener & Phillips, 2007; Maletic & Raison, 2014; Strakowski et al., 2011; Townsend et al., 2012; Whitton, Treadway, & Pizzagalli, 2015; Yoshimura et al., 2014), which suggests that the altered relationship between fT1ρ and BOLD is related to the illness. For instance, numerous studies have shown that functional activity in the striatum is altered in bipolar disorder during the completion of reward tasks (Caseras, Lawrence, Murphy, Wise, & Phillips, 2013; Whitton et al., 2015; Yip, Worhunsky, Rogers, & Goodwin, 2014) and reduced during fear perception tasks (Killgore, Gruber, & Yurgelun‐Todd, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Prescribed social interactions along with conventional medication enhance the longterm outcomes [227]. Interactive contributions of genetic, neurobiological, and psychosocial factors are involved in therapeutic regime of BD [224].…”
Section: Bipolar Disorder and Related Psychobehavioural Anomaliesmentioning
confidence: 99%
“…The occupational and social dysfunction is evident through signs of depressive symptoms, excessive alcohol use, anxiety, abnormal symptoms and degraded socioeconomic status [227]. Functional impairment can be seen between episodes and most frequently in case of subsyndromal depressive symptoms [228,223].…”
Section: Bipolar Disorder and Related Psychobehavioural Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…The task was chosen as it has been shown to differentiate BD patients and those at increased familial risk for the disorder from healthy controls with respect to differing brain activation patterns (McIntosh et al, 2008b;Whalley et al, 2011). It has also been found to activate left superior and middle prefrontal regions (Allen et al, 2010), anterior cingulate areas (NathanielJames et al, 1997), as well as the striatum (McIntosh et al, 2008b), which are considered to be involved in the pathophysiology of BD (Strakowski et al, 2005;Cerullo et al, 2009). Moreover, it probes neuropsychological deficits in verbal initiation and verbal fluency commonly observed in BD (Arts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%